Evaluating the efficiency of the spatial distribution of autism institutes in the city of Baghdad: Al-Rusafa Side as A model - Faraj , Khawla (Al-Adab Journal, 2024)
Through field research, it was found that there was inefficiency in the distribution of community centers for autism disorder in the city of Baghdad/Rusafa side, and their concentration in one municipality rather than another. In addition, the standards set by the Ministry of Labor and Social Affairs were distinguished by being fixed and within flexible conditions and controls for establishing these institutes and centers. Eligibility for autism disorder. As for the sample size, it was random by relying on the institute’s students who were actually present during the study for the year 2021-2022, and studying all of their behavior through the questions that were placed in the questionnaire form, in addition to that, questions that were related to the heads of the family of the child with autism, as It was found that most of them were earners, at a rate of (25%) of the total sample size. Most of them were forced to place their children in private autism institutes to treat their children, which costs significant amounts of money, in addition to the exorbitant costs of treatment. This is the opposite, since it was not a government institute containing these children Troubled.